Application of Wireless Technology for Control: A WirelessHART Perspective - Hassan, S.M. (Elsevier B.V., 2017)
Process monitoring and automation in the industrial sector are hitherto done over wired connection between devices. It is evident that the amount of wires required increased proportionally to the complexity of the industry and their installation is time consuming. The wires used in the industry must withstand the harsh environmental conditions, hence expensive to install and maintain. In the event of loss of connection due to accident or any other reason, the cost incurred as a result of the downtime is high. The highlighted problems necessitated the need for an open, interoperable wireless standard like WirelessHART that can overcome these problems. Three categories of applications running in any process plant with increment of criticality are for monitoring, control and safety. The current application of wireless technology including WirelessHART in the industry so far is limited to monitoring and some attempts are being made to apply it for control. This paper examines the extent to which WirelessHART technology is applied especially for the purpose of control. © 2017 The Authors.